EFL teacher self-efficacy development in professional learning communities. (June 2017) - Zonoubi, Rezvan; Eslami Rasekh, Abbas; Tavakoli, Mansoor
Abstract: Teachers' efficacy beliefs exert a significant influence on their practice and their students' learning. This study investigates the contribution of two six-month Professional Learning Community (PLC) interventions to 10 English as a Foreign Language (EFL) novice and experienced teachers' self-efficacy. The data were collected through pre and post-interviews with the participants, their reflective journals, and recordings of the PLC meetings. The findings suggest that the experienced teachers' self-efficacy improved in terms of employing innovative instructional strategies and language proficiency. An increase was also observed in the novice teachers' self-efficacy for classroom management, their autonomy, and their perceived language proficiency. Finally, the participants in both groups developed a stronger sense of professional community membership as reflected in their focus on their collective efficacy toward the end of the PLCs.